Electrochemical kinetics : theoretical and experimental aspects - Vetter, Klaus J. (Academic Press, 1967)
Electrochemical Kinetics: Theoretical Aspects focuses on the processes, methodologies, reactions, and transformations in electrochemical kinetics. The book first offers information on electrochemical thermodynamics and the theory of overvoltage. Topics include equilibrium potentials, concepts and definitions, electrical double layer and electrocapillarity, and charge-transfer, diffusion, and reaction overvoltage. Crystallization overvoltage, total overvoltage, and resistance polarization are also discussed. The text then examines the methods of determining electrochemical reaction mechanisms.